Single-cell transcriptome profiling of m6A regulator-mediated methylation modification patterns in elderly acute myeloid leukemia patients - Zhe Wang; Xin Du; Peidong Zhang; Meiling Zhao; Tianbo Zhang; Jiang Liu; Xiaolan Wang; Doudou Chang; Xiaxia Liu; Sicheng Bian; Xialin Zhang; Ruijuan Zhang (Molecular Biomedicine)
Abstract Millions of people worldwide die of acute myeloid leukaemia (AML) each year. Although N6-methyladenosine (m6A) modification has been reported to regulate the pathogenicity of AML, the mechanisms by which m6A induces dysfunctional hematopoietic differentiation in elderly AML patients remain elusive. This study elucidates the mechanisms of the m6A landscape and the specific roles of m6A regulators in hematopoietic cells of elderly AML patients. Notably, fat mass and obesity-associated protein (FTO) was found to be upregulated in hematopoietic stem cells (HSCs), myeloid cells, and T-cells, where it inhibits their differentiation via the WNT signaling pathway. Additionally, elevated YT521-B homology domain family proteins 2 (YTHDF2) expression in erythrocytes was observed to negatively regulate differentiation through oxidative phosphorylation, resulting in leukocyte activation. Moreover, IGF2BP2 was significantly upregulated in myeloid cells, contributing to an aberrant chromosomal region and disrupted oxidative phosphorylation. m6A regulators were shown to induce abnormal cell-cell communication within hematopoietic cells, mediating ligand-receptor interactions across various cell types through the HMGB1-mediated pathway, thereby promoting AML progression. External validation was conducted using an independent single-cell RNA sequencing (scRNA-Seq) dataset. The THP-1 and MV411 cell lines were utilized to corroborate the m6A regulator profile; in vitro experiments involving short hairpin RNA (shRNA) targeting FTO demonstrated inhibition of cell proliferation, migration, and oxidative phosphorylation, alongside induction of cell cycle arrest and apoptosis. In summary, these findings suggest that the upregulation of m6A regulators in HSCs, erythrocytes, myeloid cells, and T-cells may contribute to the malignant differentiation observed in AML patients. This research provides novel insights into the pathogenesis of AML in elderly patients and identifies potential therapeutic targets.